The Influence of Host miRNA Binding to RNA Within RNA Viruses on Virus Multiplication - Lei, Lin; Cheng, Anchun; Wang, Mingshu; Jia, Renyong (Frontiers in Cellular and Infection Microbiology, 2022)
microRNAs (miRNAs), non-coding RNAs about 22 nt long, regulate the post-transcription expression of genes to influence many cellular processes. The expression of host miRNAs is affected by virus invasion, which also affects virus replication. Increasing evidence has demonstrated that miRNA influences RNA virus multiplication by binding directly to the RNA virus genome. Here, the knowledge relating to miRNAs’ relationships between host miRNAs and RNA viruses are discussed.